2021
DOI: 10.1021/acsearthspacechem.1c00155
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic As(III) Oxidation Coupled with Nitrate Reduction and Attenuation of Dissolved Arsenic by Noviherbaspirillum Species

Abstract: Arsenic pollution is a worldwide problem. In flooded arsenic-contaminated paddy soils, arsenic bioavailability to rice plants is elevated due to the reductive dissolution of arsenate (As­(V)) containing Fe­(III) (oxyhydr)­oxides. However, microbial-mediated arsenite (As­(III)) and Fe­(II) oxidation has great potential for attenuating arsenic mobility in an anoxic environment. In this study, a bacterium strain HC18 belonging to the genus Noviherbaspirillum was isolated from arsenic-contaminated paddy soil. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…1 ), but most of these taxa were low in abundance with a mean relative abundance <1%. For example, Fibrobacteres is an important phylum of cellulose-degrading bacteria ( Ransom-Jones et al, 2012 ); the genus Devosia possesses bioremediation potential ( Talwar et al, 2020 ); and the denitrifying bacteria Noviherbaspirillum ( Wu et al, 2021 ) were significantly upregulated over time. The following significantly decreased over time: Firmicutes, which are plant growth-promoting bacilli ( Kumar, Khare & Dubey, 2012 ); Bacillales, which have effective biological control and biodegradation potential ( Barathi et al, 2020 ); Nitrosomonadales, which are related to sulfate and iron reduction; and Desulfuromonadales, which are an order capable of iron and sulfate reduction ( Wunder et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ), but most of these taxa were low in abundance with a mean relative abundance <1%. For example, Fibrobacteres is an important phylum of cellulose-degrading bacteria ( Ransom-Jones et al, 2012 ); the genus Devosia possesses bioremediation potential ( Talwar et al, 2020 ); and the denitrifying bacteria Noviherbaspirillum ( Wu et al, 2021 ) were significantly upregulated over time. The following significantly decreased over time: Firmicutes, which are plant growth-promoting bacilli ( Kumar, Khare & Dubey, 2012 ); Bacillales, which have effective biological control and biodegradation potential ( Barathi et al, 2020 ); Nitrosomonadales, which are related to sulfate and iron reduction; and Desulfuromonadales, which are an order capable of iron and sulfate reduction ( Wunder et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Noviherbaspirillum [80] Rhizobacter [81] Sulfurospirillum [82] Thauera [82] Vogesella [83] Nitrite oxidation Candidatus Nitrotoga [84] Nitrite reduction…”
Section: Nitrate Reductionmentioning
confidence: 99%
“…Curvibacter [98] Leptothrix [99] Noviherbaspirillum [80] Sideroxydans [100] Undibacterium [98] Fe (III) reduction…”
Section: Fe (Ii) Oxidationmentioning
confidence: 99%
“…Contamination of As in the paddy field poses a critical challenge to growers because fragrant rice is sensitive to abiotic stresses that result in yield loss and 2-AP reduction . Arsenite (As­(III)) and arsenate (As­(V)) are two forms of inorganic As, in particular, As­(V) containing Fe­(III) (oxyhydr)­oxides can be dissolved by reduction into As­(III) becoming more bioavailable in paddy field . A recent publication showed that the total As content in the rice grain increased by about 80% under continuous flooding conditions compared with aerobic conditions, suggesting negative impact of As­(III) rice.…”
Section: Introductionmentioning
confidence: 99%